2016
DOI: 10.1111/all.12915
|View full text |Cite
|
Sign up to set email alerts
|

Residential greenness is differentially associated with childhood allergic rhinitis and aeroallergen sensitization in seven birth cohorts

Abstract: Although residential greenness appears to be associated with childhood allergic rhinitis and aeroallergen sensitization, the effect direction varies by location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
126
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(135 citation statements)
references
References 30 publications
7
126
0
2
Order By: Relevance
“…31 For childhood asthma and atopy, there is some evidence though possibly restricted to specific settings with regional variation. [32][33][34] In our analysis, there was a clear gradient in population density, greenness, tree cover, and their counterpart soil sealing over the exposure strata (Figure 2). Apparently, the above pictured scenery for the farm children studies does not just seem a cliché, but was substantiated by objectively measured data.…”
Section: Discussionmentioning
confidence: 76%
“…31 For childhood asthma and atopy, there is some evidence though possibly restricted to specific settings with regional variation. [32][33][34] In our analysis, there was a clear gradient in population density, greenness, tree cover, and their counterpart soil sealing over the exposure strata (Figure 2). Apparently, the above pictured scenery for the farm children studies does not just seem a cliché, but was substantiated by objectively measured data.…”
Section: Discussionmentioning
confidence: 76%
“…More research is also needed to explain regional variations. We observed inconsistent associations by region for birth weight [12], allergic rhinitis [45], and asthma and allergy-related symptoms [26,45]. In addition, more research is required outside of North America and Europe, where most studies to date have taken place.…”
Section: Discussionmentioning
confidence: 99%
“…A study pooling data of seven cohorts from multiple countries found no associations between greenness and allergic rhinitis and aeroallergen sensitization [45]. While greenness was positively associated with allergic rhinitis in Swedish and southern German cohorts, it was negatively associated with this outcome in Dutch and northern German cohorts.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, some studies have shown that increases in the “normalized difference vegetation index” or NDVI, a measure of the greenspace in a given geographical area, is associated with decreased asthma prevalence (Sbihi, Tamburic, Koehoorn, & Brauer, ). However, other studies have shown no effects or negative effects of greenspace on asthma prevalence and control (Dadvand et al, ; Fuertes et al, ). One possible explanation for the mixed results is the failure to account for indicators of neighborhood safety, such as neighborhood violent crime rate and parent perceptions of neighborhood safety, which would affect parents’ willingness to allow their children to use greenspace.…”
Section: Introductionmentioning
confidence: 94%
“…Indeed, some studies have shown that increases in the "normalized difference vegetation index" or NDVI, a measure of the greenspace in a given geographical area, is associated with decreased asthma prevalence (Sbihi, Tamburic, Koehoorn, & Brauer, 2015). However, other studies have shown no effects or negative effects of greenspace on asthma prevalence and control (Dadvand et al, 2014;Fuertes et al, 2016).…”
mentioning
confidence: 99%